Proposed Federal/State oil and gas lease sale : Beaufort Sea - United States. Bureau of Land Management. (Washington : Dept. of the Interior, Bureau of Land Management : for sale by the Supt. of Docs., U.S. Govt. Print. Off., 1979)
At head of title: United States Department of the Interior final environmental impact statement. Includes bibliographies. Mode of access: Internet.